Implementasi Sistem Point of Sales Menggunakan Metode Agile Development - Aditya lutfi Irawan; Agung Triayudi; Agus Iskandar (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Information technology, which is developing very rapidly, can have both positive and negative impacts. With the application of this information technology can bring added value in the development of the business world. Due to the progress of the business world and the increasing needs and competition between businesses that are getting bigger. Companies are competing in using information technology to advance business and also service to customers to create a good corporate image and to outperform the business competition of other companies. The development of information and computer systems can be applied and used as a reference in designing software systems, namely Point Of Sales (POS). This point of sales software is often applied to manage store buying and selling data. Hoops Frozen Food store is engaged in selling frozen food, but Hoops Frozen Food still uses a manual sales system because the purpose of this research is to serve as a guide in designing and implementing a point of sales system that is useful in speeding up buying and selling transaction services, calculating inventory and also support the shop's business. Programming this application uses the Laravel Framework and for the database uses MySQL. The method used in the design is Agile Development and Scrum Framework to support the Hoops Frozen Food business. From the results of the analysis and evaluation of the point of sales system at Hoops Outfit, it is good at speeding up buying and selling transactions, demonstrating incoming and sold stock and also providing sales and purchase reports at stores. service to customers.